1974
DOI: 10.1055/s-0028-1093863
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclic AMP-Mediated Action of Epinephrine on the Activity of Carbonic Anhydrase in Avian Erythrocytes

Abstract: Epinephrine (0.6 respectively 1.2 mg/kg] and DBcAMP* [200 mg!kg] injected intravenously in chickens enhanced appreciably the erythrocyte carbonic anhydrase within 20 minutes. In vitro, using suspensions of erythrocytes, epinephrine had the same effect. In hemolysates with added A TP and theophylline, epinephrine (0.1 mM] as weil as fluoride (10 mM] enhance carbonic anhydrase activity up to 50% within 15 minutes. The same effect is obtained by addition of cydic AMP [90-600 J.LM].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Several earlier pieces of evi dence pointed in this direction. It is known from the pioneering work of Sutherland and his colleagues, in which they first demon strated the existence of the cAMP second messenger system, that epinephrine increases cAMP in pigeon [ The model we selected was the Japanese quail erythrocyte similar to that used by Siegmund et al [4], Earlier we had reported that in this model epinephrine increased CA activ ity by 14% [5]; the present study focused on an attempt to increase the size of this response by employing two strategies: use of the padrenergic agonist isoproterenol instead of epinephrine, and pretreatment with reserpine to decrease circulating catecholamines at the time of removal of the erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several earlier pieces of evi dence pointed in this direction. It is known from the pioneering work of Sutherland and his colleagues, in which they first demon strated the existence of the cAMP second messenger system, that epinephrine increases cAMP in pigeon [ The model we selected was the Japanese quail erythrocyte similar to that used by Siegmund et al [4], Earlier we had reported that in this model epinephrine increased CA activ ity by 14% [5]; the present study focused on an attempt to increase the size of this response by employing two strategies: use of the padrenergic agonist isoproterenol instead of epinephrine, and pretreatment with reserpine to decrease circulating catecholamines at the time of removal of the erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The following method was modified from that described by Siegmund et al [4] for chicken erythro cytes. Heparinized blood was collected by cardiac puncture from halothane-anesthctizcd birds and was centrifuged at 2,000 rpm for 15 min at 4°C.…”
Section: Incubation O F Intact Erythrocytesmentioning
confidence: 99%
See 1 more Smart Citation